White labour and the 'social democratic' movement in the Transvaal; the South African Labour Party, the South African Trades and Labour Council and their trade union affiliates, 1930 - 1954 - Touyz, Brian Martin (Department of Political Studies, 2014)
Bibliography: p.330-353.